1981
DOI: 10.3406/arsci.1981.1126
|View full text |Cite
|
Sign up to set email alerts
|

Imported and locally produced ceramics at Locri Epizephiri : results of spectrochemical analyses : chemical considerations on the thermal treatment of raw material and weathering of ceramics.

Abstract: In the important locality of Locri Epizephiri, many types of ceramics have been found. Besides clearly imported pieces of Attic and Corinthian style, others have been gathered, whose local manufacturing appeared as very probable, but not sure. In order to solve this problem, spectroanalytical methods were used able to "mark" the different types of ceramics. Some more or less defined clusters of point have been identified, corresponding to stylistically defined groups of ceramics. We also tried to establish if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…2). Studies on ceramics from Southern Italy have focused on Attic pottery found in Locri Epizephiri (Barra Bagnasco et al 1981;Mirti et al 1995) and Brutium, Calabria (Preacco Ancona, 1998, Mirti et al, 1998. Research on Calabria demonstrated that regional workshops started imitating Campanian A, B, and C, which arrived from different areas of the Italian Peninsula as well as from Sicily (Mirti et al 1995(Mirti et al , 1998Preacco Ancona 1998).…”
Section: Archaeometric Studies On Late Republican Black Gloss Pottery: a Brief Summarymentioning
confidence: 99%
“…2). Studies on ceramics from Southern Italy have focused on Attic pottery found in Locri Epizephiri (Barra Bagnasco et al 1981;Mirti et al 1995) and Brutium, Calabria (Preacco Ancona, 1998, Mirti et al, 1998. Research on Calabria demonstrated that regional workshops started imitating Campanian A, B, and C, which arrived from different areas of the Italian Peninsula as well as from Sicily (Mirti et al 1995(Mirti et al , 1998Preacco Ancona 1998).…”
Section: Archaeometric Studies On Late Republican Black Gloss Pottery: a Brief Summarymentioning
confidence: 99%
“…A meaningful example is the district of Centocamere, part of the archaeological park of Lokroi Epizefiri, in Calabria (Southern Italy). According to archaeologists, this retail agglomeration was specialized in ceramic manufacturing, and was located close to the city gates (Barra Bagnasco et al, 1981) (Figure 1). A justification of this location might lie in the easier transport of raw materials to the production facilities combined with dispersion of smoke away from the city center to avoid the pollution generated during the crafting of ceramics.…”
Section: Retailing In Magna Graecia From the 6 Th Century Bce To The mentioning
confidence: 99%
“…Thus a scientific study of the fine ware excavated on the site was initiated. First, a semi-quantitative analysis of suspected local and imported sherds was carried out by optical emission spectroscopy (OES) and X-ray fluorescence (XRF) and confirmed the visual classification, but for two 'imported' and one 'local' piece (Barra Bagnasco et al 1980). This paper reports on a more recent series of analyses performed on new samples by inductively coupled plasma optical emission spectroscopy (ICPOES).…”
Section: Introductionmentioning
confidence: 95%